Index Based Livestock Insurance (IBLI) Marsabit Household Survey - Alulu, Vincent; Jensen, Nathaniel D.; Ikegami, Munenobu (International Livestock Research Institute, 2023)
These data contain seven rounds of a longitudinal, socio-economic survey of 924 pastoral households from Marsabit County Kenya, collected between 2010 and 2020.